Assessment of antibacterial properties of newer dentin bonding agents: An in vitro study - Pavitra B Sampath; Mithra N Hegde; Priyadarshini Hegde (Wolters Kluwer Medknow Publications, 2011)
Aim: To evaluate and compare the antibacterial activity of newer dentin bonding agents on Streptococcus mutans using the direct contact test. Materials and Methods: Streptococcus mutans was used as test organism and a direct contact test was performed. The dentin bonding agents to be tested were grouped as Group I, Clearfil Protect Bond, Group II, Adper Easy One, and Group III, Prime and Bond NT. For the direct contact test, three microtiter plates consisting of 96 wells each were taken (288 wells). These wells were divided into three groups of 96 wells; 16 wells of a microtiter plate were utilized, of which four were designated as 'A' wells (with the dentin bonding agent and bacterial suspension), another four as 'B' wells (without the dentin bonding agent, but with the bacterial suspension), another four as the 'C' wells (with the tested material, but without bacteria, which served as the negative control), and the remaining four as the 'D' wells (without the dentin bonding agent, which served as the positive control). Each group was treated with their respective bonding agents as per the manufactures instructions. Broth of 15 mL was then transferred from the A wells into an adjacent set of B wells containing fresh medium (215 mL). This resulted in two sets of four wells for each tested material containing an equal volume of liquid medium, so that bacterial growth was monitored both in the presence and in the absence of the tested material. The plate was placed for incubation at 37°C in the microplate reader and the optical density in each well was measured at 600 nm. The readings were taken at regular intervals. (Every 30 minutes for 16 hours). Results: The Dentin bonding agents evaluated in this study showed different inhibitory effects. Clearfil Protect Bond and Prime and Bond NT were most effective, and Adper Easy One was least effective against Streptococcus mutans. Interpretation and Conclusion: The Dentin bonding agents evaluated in this study showed different inhibitory effects. Clearfil Protect Bond and Prime and Bond NT were most effective, and Adper Easy One was the least effective against Streptococcus mutans. Hence, the incorporation of antibacterial agents into the dentin bonding agents may become an essential factor in inhibiting residual bacteria in the cavity and secondary caries.